Pengaruh Servant Leadership terhadap Organizational Citizenship Behavior (OCB) melalui Kepuasan Kerja pada Pegawai Badan Pengelola Pajak dan Retribusi Daerah (BPPRD) Kota Jambi - Rika Puspasari (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to analyze the effect of taxes on regional spending in Jambi Province and to analyze the effect of levies on regional spending in Jambi Province. This study uses a multiple linear regression analysis tool. The development of regional taxes in Jambi Province has fluctuated with the average development of regional taxes in Jambi Province from 2011-2021 of 7.13 percent. The development of regional fees in Jambi Province has fluctuated with the average development of regional fees in Jambi Province from 2011-2021 amounting to -3.06 percent. Meanwhile, the development of regional spending in Jambi Province has fluctuated with the average development of regional spending in Jambi Province from 2011-2021 amounting to 10.58 percent. The results of the study show that regional taxes and regional levies simultaneously have a significant effect on regional spending in Jambi province during the 2011-2021 period. Then partially Regional Taxes and Regional Levies also have a significant effect on Regional Expenditure in Jambi Province.